Boekbesprekings/Book Reviews - Venter, P. M. (HTS teologiese studies, 2008)
Enoch and Qumran origins: New light on a forgotten connection The life of a Galilean Shaman: Jesus of Nazareth in anthropological perspectiveDarwin’s nemesis: Phillip Johnson and the intelligent design movementThe new perspective on Paul: Collected essaysSlavery in Early ChristianityBiblische Gestalten bei den Kirchenvätern: Adam (Biblische Gestalten bei den Kirchenvätern)Lutheran questions, Lutheran answers: Exploring Christian faithBethlehem besieged: Stories of hope in times of troubleNaar een nieuwe kerkenraad (Apeldoornse Studies, no 48)“Stärker als Männer und tapferer als Ritter”: Pilgerinnen in Spätantike und MittelalterThe end of wisdom: A reappraisal of the historical and canonical function of EcclesiastesVerzameld Werk, deel I: De aard van de theologie (Besorgd door Dr D van Keulen)Augustinus – Belydenisse: Getuienis oor ’n lewe in GodLiefde is die grootste: Oor erotiek en seksualiteit